Adolescent Basic Facial Emotion Recognition Is Not Influenced by Puberty or Own-Age Bias - Vetter, Nora C.; Drauschke, Mandy; Thieme, Juliane; Altgassen, Mareike (Frontiers in Psychology, 2018)
Basic facial emotion recognition is suggested to be negatively affected by puberty onset reflected in a “pubertal dip” in performance compared to pre- or post-puberty. However, findings remain inconclusive. Further, research points to an own-age bias, i.e. a superior emotion recognition for peer faces. We explored adolescents’ ability to recognize specific emotions. Ninety-five children and adolescents, aged 8 to 17 years, judged whether the emotions displayed by adolescent or adult faces were angry, sad, neutral, or happy. We assessed participants a priori by pubertal status while controlling for age. Results indicated no “pubertal dip”, but decreasing reaction times across adolescence. No own-age bias was found. Taken together, basic facial emotion recognition does not seem to be disrupted during puberty as compared to pre- and post-puberty.